Ανάλυση κατασκευών πολύπλοκης γεωμετρίας με την ισογεωμετρική μέθοδο - Karaiskos, Georgios (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής. Εργαστήριο Στατικής και Αντισεισμικών Ερευνών, 2015)
The scope of this thesis is the actual implementation of Linear Static Isogeometric Analysis, (an innovative methodology of complete CAD – CAE integration introduced by J. Austin Cottrell, Thomas J.R. Hughes and Yuri Bazilevs) to real engineering structures with complicated geometry. NURBS models have been analyzed assuming linear elasticity. Finite Element Method and Non-Uniform Rational B-SPLines have been examined separately, as the two components of Isogeometric Analysis. The routines, which have been used for the linear static analysis of the presented applications, were developed in the high-level language “C++” and “OpenGL” on the interactive environment of well known Open Source Software. Additionally, geometrical representations were acquired through the NURBS-based software “Rhinoceros 3D” and “Maya”. The topics considered are B-SPLine and NURBS entity properties, Refinement techniques, Stiffness Matrix Formulation, result post-processing (displacement, stress, and strain field) and linear 2D and 3D applications investigating models of various representations.